Compression hemostasis using fully covered self-expandable metallic stents for refractory hemorrhages caused by esophageal cancer: A pilot study - Bi, Yonghua; Ren, Jianzhuang; Han, Xinwei (Frontiers in Gastroenterology, 2023)
Objective: Full covered self-expandable metallic stent (SEMS) has been widely used as a salvage therapy for patient with esophageal variceal bleeding. However, the role of fully covered SEMS has not established in the management of hemorrhage caused by esophageal cancer. We aimed to investigate the safety and efficacy of fully covered SEMS for esophageal cancer–related hemorrhage. Methods: From September 2019 to March 2022, 17 patients underwent insertion of fully covered SEMS for malignant esophageal hemorrhages were retrospectively analyzed. The chest computed tomography (CT) scan and esophagography were performed routinely to show the location and length of esophageal cancer. A fully covered SEMS was implanted under fluoroscopy. Baseline demographics were retrospectively collected, including gender, age, previous treatment, comorbidities, lesion type, and stent size. Results: A total of 20 metal stents were placed in 17 patients, with a technical success rate of 100% and hemostasis success rate of 88.2%. Stent removal was performed in 3 patients due to complications. None of perioperative deaths were related to stent placement or removal. A total of 5 main complications (29.4%) were found after stent insertion. Stent migration and restenosis were observed in 2 patients (11.8%). Except for two perioperative deaths and one patient lost to follow-up, all remained 14 patients were successfully followed up. Two patients survived without obvious symptom; 12 patients were dead due to tumor progression (n=10), severe infection (n=1) and cerebrovascular accident (n=1). The median overall survival was 13.8 months. Conclusion: Insertion of fully covered SEMS is safe and effective for the salvage management of refractory esophageal cancer–related hemorrhage, and may be a way forward toward its innovative use of compression hemostasis.